ASPECTOS ELETROFISIOLÃ“GICOS EM LARVAS DE ð˜ˆð˜ð˜¢ð˜£ð˜¢ð˜®ð˜¢ ð˜¢ð˜³ð˜¨ð˜ªð˜ð˜ð˜¢ð˜¤ð˜¦ (HUBNER, 1818) INFECTADAS PELO VÃRUS DA POLIEDROSE NUCLEAR - Andrade, C. F. S.; Britto, L. R. G.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
ASPECTOS ELETROFISIOLÃ“GICOS EM LARVAS DE ð˜ˆð˜ð˜¢ð˜£ð˜¢ð˜®ð˜¢ ð˜¢ð˜³ð˜¨ð˜ªð˜ð˜ð˜¢ð˜¤ð˜¦ (HUBNER, 1818) INFECTADAS PELO VÃRUS DA POLIEDROSE NUCLEAR